Bilateral isokinetic concentric and eccentric strength profiles of the knee extensors and flexors in young soccer players - Kellis, S.; Gerodimos, V.; Kellis, E.; Manou, V. (2001)
Isokinetic dynamometers are extensively used to monitor strength development in young soccer players. The purpose of this study was to examine the effects of age, velocity and leg of preference on the peak moments in young soccer players. One hundred and fifty eight soccer players (age = 13.2 ± 2.1 years; height = 1.6 ± 1.4; body mass = 51.6 ± 14.89 kg) performed maximum knee extension and flexion efforts at 30^{°}/s, 90^{°}/s, 120^{°}/s and 180^{°}/s of both legs and under eccentric and concentric conditions. The absolute (Nm) and the relative (Nm/Kg) peak moment of forces were further analyzed. Four-way analysis of variance designs were applied to examine the effects of age, angular velocity, leg of preference and muscle action (eccentric -- concentric) on the recorded moments for knee extension and flexion. The isokinetic moment of force of knee extensors ranged from 1.01 ± 0.19 to 3.58 ± 0.50 Nm/kg. The knee flexion moments ranged from 0.95 ± 0.16~Nm/kg to 2.42 ± 0.59 Nm/kg. For all testing conditions eccentric moments were greater than the corresponding concentric (p<0.05). The isokinetic moment under all testing conditions increased significantly (p<0.05) as chronological age increased from 10 to 18 years. Furthermore, the isokinetic moment of the preferred leg, collapsed for the effects of age, angular velocity and muscle action, was significantly greater compared to the moments of the other leg. The strength profiles developed in the present study can assist in the establishment of baseline data in young soccer players. Isokinetics and Exercise Science, Issue: Volume 9, Number 1/2001, Pages: 31 - 39